Healthcare-associated infections: a ten-year bibliometric analysis - Ismaeil, Rehab A.; Fata Nahas, Abdul Rahman; Kamarudin, Norhidayah; Mat Nor, Mohd Basri; Abubakar, Usman; Nik Mohamed, Mohamad Haniki (EManuscript Technologies, 2023)
Healthcare-Associated Infections (HCAIs) pose a significant threat to the safety of patients and Healthcare Workers (HCWs). HCAIs increase morbidity and mortality, as well as healthcare costs. Therefore, prevention is a key goal for healthcare organisations and systems. In this regard, this study aims to conduct a bibliometric analysis of research and review papers published in journals indexed in the PubMed database between 2013 and 2023 on HCAIs in order to investigate areas of concentration and developing trends in the field. There was a total of 356 core zone publications, and the number of articles published is expected to reach its high in 2020. Most of the papers were found to have been published in the journals of hospital infection and antibiotic resistance and infection control. European countries conduct the most and more collaborative scientific research in this area, followed by the United States, Australia, and China. Surveillance, infection control, hand hygiene and COVID-19 represent the leading frontiers and research hotspots for HCAIs. HCAIs and Infection Prevention and Control (IPC) also co-occurred in most of the study discussions. The analysis is expected to yield meaningful data by illuminating the overall structure and direction of previous research on HCAIs, as well as by providing important ideas for future research.